The management of corneal graft rejection - Hill, John Clifford (Department of Medicine, 2025)
Descriptions of corneal disease and suggested treatments have been documented since the ancient civilisations of Egypt and Greece. However, in these cultures corneal surgery was limited to various types of superficial keratectomy. The idea of corneal grafting was suggested relatively recently3,4• Guillaume Pellier de 22 Quengsy5, a Frenchman, suggested in 1789 the complete replacement of the opaque cornea using a thin glass disc the size of the cornea and set in a silver rim. He suggested that it could be stitched in with cotton threads and designed instruments for the operation although he never performed the procedure himself. This idea was really the forerunner of the modem keratoprothesis. At the end of the 18th and beginning of the 19th century there was a stimulus for corneal grafting as a result of blindness from diseases such as smallpox, venereal disease, and trachoma brought back by soldiers in the Napoleonic wars. It is uncertain who first suggested the replacement of damaged corneas with living tissue, but the credit is usually attributed to Franz Reisinger6 who also coined the term 11 keratoplasty11 • Reisinger confined his work to rabbits and chickens but most grafts failed either from opacification or sepsis. His work, however, did stimulate debate over the feasibility of keratoplasty, but many were extremely sceptical including one of Berlin's great surgeons of the time, Dieffenbach. He wrote in 18312 that Reisinger's idea of keratoplasty was 11 ••• certainly one of the most audacious fantasies, and it would be the highest reward of surgery if this operation succeeded 11 •